2000
DOI: 10.1038/sj.cgt.7700221
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli thymidylate synthase expression protects human cells from the cytotoxic effects of 5-fluorodeoxyuridine more effectively than human thymidylate synthase overexpression

Abstract: In this study, we compared the relative abilities of human thymidylate synthase (hTS) and Escherichia coli thymidylate synthase (eTS) expression to confer resistance to the cytotoxic effects of treatment with the TS inhibitor 5-fluorodeoxyuridine (FdUrd). G418-selected clones expressing either form of the protein were significantly more resistant than the lacZ-expressing clone, VALZ2, to FdUrd-induced cytotoxicity. Although eTS-expressing clones expressed 2-to 3-fold more TS protein than hTS-overexpressing clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We showed previously that a P254L variant of ecTS conferred substantially greater resistance to FdUrd and raltitrexed (.100-fold) than the analogous P303L mutant of human TS (Fantz et al, 2000). In addition, Parsels et al (2000) showed that expression of ecTS in human VA13 cells conferred greater protection against FdUrd in the presence of leucovorin compared with human TS. We hoped to exploit these naturally occurring differences in designing chemoresistant TS genes for gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that a P254L variant of ecTS conferred substantially greater resistance to FdUrd and raltitrexed (.100-fold) than the analogous P303L mutant of human TS (Fantz et al, 2000). In addition, Parsels et al (2000) showed that expression of ecTS in human VA13 cells conferred greater protection against FdUrd in the presence of leucovorin compared with human TS. We hoped to exploit these naturally occurring differences in designing chemoresistant TS genes for gene therapy.…”
Section: Discussionmentioning
confidence: 99%